ALTERNATIVE IN FUELS WORKING, SPARK GRASS TO BE REMOVED AND DIESEL ENGINES HEAT ACCOUNT PROGRAM CREATE - Axmatjanov Ravshanjan Nematjonovich; Nosiraliev Ismailjon Usmanali o’g’li (Journals Park Publishing, 2024)
By developing software for thermal calculation of spark ignition engines and diesel engines operating on alternative fuels, it allows analyzing the process of operation of engines on any fuel using computer programs in the field of engine building, improvement of internal combustion engines (ICE) and research, development of candidate and diploma projects, course projects on the topic "Internal combustion engines" and get results, as well as study the thermal calculation of the internal combustion engine.
Keywords: engines, alternative fuels, spark-ignition engines, diesel engines, modern information technologies, programming, calculation, experiment, analysis, synthesis.